Motives for demand for religion: a confirmatory factor analysis - A Somasundram, Sotheeswari; Habibullah, Muzafar Shah (School of Social Sciences, Universiti Sains Malaysia, 2016)
This study investigates the motivation for religious demand among Christians using the International Social Survey Program (ISSP) data on Religion for 2008. This study using both exploratory and confirmatory factor analysis identified two motives, afterlife motive and the current life motive that influences demand for religion. The afterlife motive, aligned to the Christian doctrine of belief in afterlife, heaven and hell, was one of the dimensions of motives for religious demand. For gains in the current life, although the various studies highlight two construct of personal gains and social gains, however, for this study, all items loaded onto only one construct, which is broadly termed as current life motives where religion is said to provide solace, inner peace; as well as social support and networking opportunities.